High-reliability composite solder paste and preparation and use methods thereof
By adding nano/micro antimony powder and specific solder paste to the solder paste, the problem of poor reliability of traditional solder paste in high-temperature environments is solved, the effect of low-temperature welding and high-temperature service is achieved, and the cost is reduced. It is suitable for high-temperature and high-temperature high-temperature service. Electronic components required for reliability.
Patent Information
- Application Number
- CN202411335276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional solder paste is difficult to maintain reliability in high temperature environments, especially for automotive motor control systems for third-generation semiconductor materials. Common solder is prone to cracks and fatigue failure during extreme temperature cycles, and the use of existing high melting point solders is affected by Material compatibility and cost limitations, low-cost and high-reliability welding materials are difficult to achieve.
A composite solder paste is adopted, including tin-based alloy powder, nano/micro-antimone antimony powder and solder paste. The solder paste contains film-forming substances, organic amides, organic carboxylic acids, silicone surfactants, organic solvents, and organic amines. Halogenated and alkylimidazoline corrosion inhibitors, nano/micro antimony powder diffuses after tin-based alloy melting to enhance the melting point of the solder, and improves soldering performance through specific mixing and deoxidation treatments.
It realizes the effect of low-temperature welding and high-temperature service, while reducing costs, is suitable for large-scale production, is suitable for harsh application environments, and the soldered composite solder paste has a higher melting point and strength, and is suitable for electronics with high temperature and high reliability requirements. Components.
Smart Images

Figure CN119188014A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, and in particular to a high-reliability composite solder paste and a preparation and use method thereof. Background Art
[0002] With the rapid development of the modern electronic industry, new electronic products are constantly emerging, and electronic equipment is developing in the direction of being light, thin and small. As a key material in the electronics industry, solder paste plays a vital role in the assembly process of electronic components. Solder paste is a mixture of flux and solder powder. The flux contains a variety of active components, which are mainly used to remove oxides on the surface of solder powder and pads during the soldering process and improve the spreadability of solder.
[0003] In order to achieve the ideal soldering effect, the flux in traditional solder paste often contains highly active chemical components. These active components are easy to react with the oxides on the surface of the solder powder at room temperature, resulting in deterioration of the solder paste such as "drying out". In particular, with the miniaturization of electronic components, the particle size of solder powder becomes smaller, and the content of oxides on its surface also increases accordingly, which further aggravates the deterioration of solder paste. The deteriorated solder paste will significantly reduce its wettability and soldering performance, and may even be unusable.
[0004] In the automotive field, with the widespread application of third-generation semiconductor materials (such as silicon carbide and gallium nitride), power semiconductor modules in automotive motor control systems must cope with more stringent working environments. These modules not only need to operate stably under high temperature conditions, but also have higher reliability. The traditional temperature cycle test conditions have been increased from -40℃ to 125℃ to -40℃ to 150℃, which places higher requirements on the durability of welding materials. Common low-melting point solders (such as SAC305, the main component of which is Sn-Ag-Cu) are often difficult to withstand in these extreme temperature cycles, and are prone to cracks and fatigue failures, resulting in reduced module reliability. Although high-melting point solders (such as SnSb5) have improved in high temperature resistance, the required welding temperature exceeds 240℃, which places higher requirements on the compatibility of module materials, and the existing material selection and restrictions often make it impossible to use such solders.
[0005] In order to solve this problem, low-temperature welding materials such as nanosilver paste came into being. Nanosilver paste has excellent thermal conductivity and high-temperature service capability. It can achieve high-strength welding at low temperatures and exhibit excellent stability in high-temperature environments. However, the high cost of nanosilver paste limits its large-scale application, especially in the cost-sensitive automotive industry, which has become a major obstacle. Therefore, although nanosilver paste provides a possible solution to the challenges facing current solders, its high cost makes it impossible to completely replace existing conventional solders. In this context, the automotive industry still needs to find or develop welding materials that can meet high temperature and high reliability requirements and are cost-effective to meet the new challenges brought by the third-generation semiconductor materials. Summary of the invention
[0006] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a highly reliable composite solder paste and a preparation and use method thereof.
[0007] The technical solution adopted by the present invention to solve its technical problem is: a high-reliability composite solder paste, including tin-based alloy powder, nano / micron antimony powder, and flux paste, wherein the flux paste includes: film-forming substance, organic amide, organic carboxylic acid, silicone surfactant, organic solvent, organic amine halide, and alkyl imidazoline corrosion inhibitor.
[0008] As a further improvement of the present invention: the film-forming substance includes at least one of hydrogenated rosin and polymerized rosin; the organic amide includes octadecanoyl amide, and the organic carboxylic acid includes at least one of malic acid, salicylic acid, and adipic acid; the organic solvent includes at least one of 3-dimethylamino-1,2-propylene glycol and dipropylene glycol butyl ether; the organic amine halide includes at least one of 2,3,4,5-tetrachloroaniline, 2,6-dibromo-3,4-dichloroaniline, ethylenediamine hydrochloride, triethanolamine hydrochloride, and diphenylguanidine hydrobromide; the alkyl imidazoline corrosion inhibitor includes at least one of lauryl hydroxyethyl imidazoline, dodecyl imidazoline, oleyl hydroxyethyl imidazoline, and heptadecyl imidazoline.
[0009] As a further improvement of the present invention: the tin-based alloy powder is a Sn-Ag-Cu alloy.
[0010] As a further improvement of the present invention: the content of the nano / micron antimony powder, measured by mass percentage, accounts for 1.5%-25% of the composite solder paste; the particle size of the nano / micron antimony powder is less than or equal to 150 μm.
[0011] As a further improvement of the present invention: the content of the nanometer / micrometer antimony powder, measured by mass percentage, accounts for 4%-10% of the composite solder paste.
[0012] As a further improvement of the present invention, it also includes high melting point alloy powder, and the particle size of the high melting point metal powder ranges from 0.05 to 0.5 mm.
[0013] The present invention also includes a method for preparing a high-reliability composite solder paste using the above-mentioned high-reliability composite solder paste, comprising the following steps:
[0014] After any two of the tin-based alloy powder, nanometer / micrometer antimony powder and solder paste are mixed and stirred, they are mixed and stirred with a third one, or the tin-based alloy powder, nanometer / micrometer antimony powder and solder paste are mixed and stirred at the same time.
[0015] As a further improvement of the present invention: the oxide film on the surface of the nanometer / micrometer antimony powder needs to be removed before mixing and stirring.
[0016] The present invention also includes a method for using a high-reliability composite solder paste using the high-reliability composite solder paste described above, wherein the composite solder paste is printed or dispensed on a welding position, placed on a heating device, heated to a temperature above the melting point of the tin-based alloy powder, kept warm in an atmosphere, nitrogen or vacuum environment, and cooled to obtain a welding joint.
[0017] As a further improvement of the present invention: during the welding process, the peak temperature is 225° C.-250° C., and the heat preservation time is 1-30 minutes.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a highly reliable composite solder paste, which has the effects of low-temperature welding and high-temperature service, and at the same time is low-cost and suitable for large-scale production by enterprises. At the same low-temperature welding temperature, it is more suitable for harsh application environments than conventional solders. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solution, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0020] Figure 1 It is a graph showing the experimental results of Examples 1 to 10 of the present invention and a comparative example. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0023] Existing high melting point solders (such as SnSb5) have improved high temperature resistance, but the required welding temperature exceeds 240°C, which places higher requirements on the compatibility of module materials, and existing material selection and restrictions often make it impossible to use such solders. In order to solve this problem, low temperature welding materials such as nano silver paste have emerged. Nano silver paste has excellent thermal conductivity and high temperature service capability, can achieve high-strength welding at low temperatures, and exhibits excellent stability in high temperature environments. However, the high cost of nano silver paste limits its large-scale application, especially in the cost-sensitive automotive industry, which has become a major obstacle. In order to solve the above problems, the present invention provides a high-reliability composite solder paste and its preparation and use methods.
[0024] The present invention is further described in conjunction with the accompanying drawings and embodiments: a high-reliability composite solder paste, comprising tin-based alloy powder, nano / micron antimony powder, and flux paste, wherein the flux paste comprises: a film-forming substance, an organic amide, an organic carboxylic acid, an organosilicon surfactant, an organic solvent, an organic amine halide, and an alkyl imidazoline corrosion inhibitor.
[0025] Furthermore, tin-based alloy powder and solder paste are often the main components of solder paste, and nano / micron antimony powder is added to form a composite solder paste. After the nano / micron antimony powder is added, it will diffuse into the solder matrix after the tin-based alloy powder is melted during use, thereby increasing the melting point of the solder matrix. In addition, after welding, although the nano / micron antimony powder is not completely diffused into the molten solder matrix and then solidified to precipitate an intermediate phase or a tin solid solution, the outer shell of the nano / micron antimony powder reacts with the solder matrix to a certain extent, and is dispersed in the solder matrix like a second phase, thus forming a new alloy and increasing the melting point of the solder matrix. At the same time, the undiffused nano / micron antimony powder is dispersed in the solder matrix, hindering the slip of dislocations and increasing the strength of the solder matrix. The reason for choosing nano / micron antimony powder instead of other metal powders such as Ag and Cu is that the diffusion and dissolution of antimony element will increase the solid phase point of the solder matrix. According to the phase diagram, even if other elements are completely diffused into the solder matrix, they can only increase the liquidus point of the solder matrix and expand the melting range of the solder matrix, but cannot increase the solid phase point of the solder matrix.
[0026] As an embodiment of the present invention, the tin-based alloy powder is a Sn-Ag-Cu alloy.
[0027] Furthermore, in lead-free tin-based alloys, the melting points of Sn-Bi and Sn-In alloys are below 200°C. Even if the added nano / micron antimony powder is completely diffused into the alloy, it is difficult to raise the melting point of the overall solder matrix to above 220°C. The lowest temperatures of Sn-Cu and Sn-Ag alloys are eutectic alloys SnCu0.7 and SnAg3.5, with melting points of 227°C and 221°C respectively. Although these are acceptable, they are not as low as the melting point (217°C) of Sn-Ag-Cu eutectic alloy SnAg3Cu0.5. Therefore, Sn-Ag-Cu alloys are better as tin-based alloy powders. The selection of tin-based alloy powders needs to consider whether the melting point of the alloy formed after the nano / micron antimony powder is completely diffused into the tin-based alloy powder is raised, and also the melting point of the tin-based alloy powder needs to be considered, which determines the use temperature of the composite solder paste, and finally obtains the effect of effective low-temperature welding and high-temperature service.
[0028] As an embodiment of the present invention, the content of nanometer / micrometer antimony powder, measured by mass percentage, accounts for 1.5%-25% of the composite solder paste.
[0029] Furthermore, too high a content of nano / micro antimony powder will lead to poor welding performance of the composite solder paste, affect the diffusion temperature and time of the nano / micro antimony powder, increase the void rate of the welded joint, and at the same time, the joint after welding will be too brittle, affecting its reliability; too low a content of nano / micro antimony powder will result in the melting point of the solder matrix not being improved after welding.
[0030] As an embodiment of the present invention, the particle size of the nano / micron antimony powder is less than or equal to 150 μm.
[0031] Furthermore, excessive nano / micro antimony powder content will affect the diffusion temperature and diffusion time of the nano / micro antimony powder, thereby affecting the use of the composite solder paste, making it impossible to achieve low-temperature welding and high-temperature service effects, and will also affect the printability of the composite solder paste.
[0032] As an embodiment of the present invention, the film-forming substance includes at least one of hydrogenated rosin and polymerized rosin; the organic amide includes octadecanoyl amide, and the organic carboxylic acid includes at least one of malic acid, salicylic acid, and adipic acid; the organic solvent includes at least one of 3-dimethylamino-1,2-propylene glycol and dipropylene glycol butyl ether; the organic amine halide includes at least one of 2,3,4,5-tetrachloroaniline, 2,6-dibromo-3,4-dichloroaniline, ethylenediamine hydrochloride, triethanolamine hydrochloride, and diphenylguanidine hydrobromide; the alkyl imidazoline corrosion inhibitor includes at least one of lauryl hydroxyethyl imidazoline, dodecyl imidazoline, oleyl hydroxyethyl imidazoline, and heptadecanediazole.
[0033] As an embodiment of the present invention, it also includes high melting point metal powder, the melting point of the high melting point metal powder is above 900° C., and the particle size of the high melting point metal powder ranges from 0.05 to 0.5 mm.
[0034] The main purpose of adding high melting point metal powder is to control the height of the weld, especially in applications that require pressurization, to prevent the solder from overflowing after melting. The high melting point alloy powder needs to have a melting point above 900°C to prevent excessive diffusion in the solder matrix, causing it to lose its original design effect. The particle size range is 0.05-0.5mm, and the particle size is mainly selected based on the design height of the weld.
[0035] As an embodiment of the present invention, the content of nanometer / micrometer antimony powder, measured by mass percentage, accounts for 4%-10% of the composite solder paste.
[0036] The experimental results show that the melting point of the solder matrix after soldering with a composite solder paste containing 1.5% nano / micro antimony powder has not increased significantly, and the void morphology of the composite solder paste containing 25% nano / micro antimony powder has changed from bubble to fish scale, indicating that the wettability of the composite solder paste with this content is getting worse. Therefore, it can be known that the composite paste with a nano / micro antimony powder content of 4%-10% is more effective.
[0037] The present invention also includes a method for preparing a high-reliability composite solder paste, comprising the following steps:
[0038] After any two of the tin-based alloy powder, nanometer / micrometer antimony powder and solder paste are mixed and stirred, they are mixed and stirred with a third one, or the tin-based alloy powder, nanometer / micrometer antimony powder and solder paste are mixed and stirred at the same time.
[0039] As an embodiment of the present invention, the preparation method provided by the present invention can be divided into the following five situations: first, tin-based alloy powder and nano / micron antimony powder are mixed and stirred to form a mixed powder, and then flux paste is added for mixing and stirring to form a composite solder paste; first, tin-based alloy powder and flux paste are mixed and stirred to form solder paste, and then nano / micron antimony powder is added for mixing and stirring to form a composite solder paste; first, nano / micron antimony powder and flux paste are mixed and stirred to form antimony paste, and then tin-based alloy powder is added for mixing and stirring to form a composite solder paste; tin-based alloy powder, nano / micron antimony powder and flux paste are mixed and stirred at the same time to directly form a composite solder paste; first, tin-based alloy powder and flux paste are mixed and stirred to form solder paste, and then nano / micron antimony powder and flux paste are mixed and stirred to form antimony paste, and finally, corresponding amounts of solder paste and antimony paste are taken in proportion and mixed and stirred to form a composite solder paste, and the solder paste used for mixing and stirring the solder paste and the antimony paste can be the same or different.
[0040] As an embodiment of the present invention, before the above mixing and stirring, the oxide film on the surface of the nano / micro antimony powder is first removed.
[0041] Furthermore, the removal of the oxide film on the surface of the antimony powder depends on the degree of oxidation of the antimony powder surface. When the antimony powder is at the nano level, the surface oxidation is serious. At this time, it is necessary to add a corresponding film remover to reduce the obstruction of the oxide film during welding of the antimony powder and enable better diffusion.
[0042] The present invention also includes a method for using a high-reliability composite solder paste, which includes printing or dispensing the composite solder paste on a welding position, placing the composite solder paste on a heating device, heating the composite solder paste to a temperature above the melting temperature of the tin-based alloy powder, keeping the temperature in an atmosphere, nitrogen or vacuum environment, and cooling the composite solder paste to obtain a welding joint.
[0043] As an embodiment of the present invention, during the welding process, the peak temperature is 225° C.-250° C., and the holding time is 1-30 minutes.
[0044] Embodiment 1:
[0045] Tin-based alloy SnAg3Cu0.5 powder and flux paste A are mixed and stirred in proportion to form solder paste, and then nano / micro antimony powder with an average particle size of 50 μm is mixed and stirred with the above solder paste in proportion to form a composite solder paste. According to mass percentage, the nano / micro antimony powder in the composite solder paste accounts for 1.5% of the composite solder paste.
[0046] Among them, flux paste A includes the following ingredients: 65 parts of polymerized rosin, 18 parts of dipropylene glycol butyl ether, 5 parts of octadecyl amide, 5 parts of malic acid, 5 parts of adipic acid, 0.2 parts of silicone surfactant, 0.5 parts of 3-dimethylamino-1,2-propylene glycol, 0.1 parts of 2,3,4,5-tetrachloroaniline, 0.4 parts of 2,6-dibromo-3,4-dichloroaniline, 0.5 parts of lauryl hydroxyethyl imidazoline, and 0.3 parts of dodecyl imidazoline.
[0047] Embodiment 2:
[0048] Tin-based alloy SnAg3Cu0.5 powder and flux paste B are mixed and stirred in proportion to form solder paste, nano / micro antimony powder with an average particle size of 50 μm and flux paste C are mixed and stirred in proportion to form antimony paste, and then the solder paste and antimony paste are mixed and stirred in proportion to form a composite solder paste, in which the nano / micro antimony powder in the composite solder paste accounts for 4% of the composite solder paste in terms of mass percentage.
[0049] Among them, solder flux B includes the following ingredients: 20 parts of hydrogenated rosin, 30 parts of polymerized rosin, 30 parts of dipropylene glycol butyl ether, 8 parts of octadecyl amide, 4 parts of malic acid, 3 parts of salicylic acid, 3 parts of adipic acid, 0.4 parts of silicone surfactant, 1 part of 3-dimethylamino-1,2-propylene glycol, 0.1 parts of 2,3,4,5-tetrachloroaniline, 0.2 parts of ethylenediamine hydrochloride, 0.1 parts of dodecyl imidazoline, and 0.2 parts of oleyl hydroxyethyl imidazoline.
[0050] The soldering paste C includes the following ingredients: 30 parts of hydrogenated rosin, 30 parts of polymerized rosin, 20 parts of dipropylene glycol butyl ether, 5 parts of octadecylamide, 5 parts of salicylic acid, 7 parts of adipic acid, 0.5 parts of silicone surfactant, 2 parts of 3-dimethylamino-1,2-propylene glycol, 0.2 parts of lauryl hydroxyethyl imidazoline, and 0.3 parts of heptadecanediol imidazoline.
[0051] Embodiment 3:
[0052] Nano / micro antimony powder with an average particle size of 150 μm, tin-based alloy SnAg3Cu0.5 powder and solder paste D are mixed and stirred in proportion to prepare a composite solder paste. In terms of mass percentage, the nano / micro antimony powder in the composite solder paste accounts for 4% of the composite solder paste.
[0053] Among them, solder paste D includes the following effective ingredients: 55 parts of hydrogenated rosin, 30 parts of dipropylene glycol butyl ether, 2 parts of octadecylamide, 3.4 parts of malic acid, 8 parts of salicylic acid, 1 part of silicone surfactant, 0.3 parts of heptadecanedimidazoline, and 0.3 parts of dodecylimidazoline.
[0054] Embodiment 4:
[0055] First, nano / micron antimony powder with an average particle size of 200nm is added to a film remover to remove the surface oxide film, and then it is mixed with flux paste E in proportion to make antimony paste, and finally, tin-based alloy SnAg3Cu0.5 powder and the above antimony paste are mixed in proportion to make a composite solder paste. According to the mass percentage, the nano / micron antimony powder in the composite solder paste accounts for 4% of the composite solder paste.
[0056] Among them, solder paste E includes the following ingredients: 50 parts of hydrogenated rosin, 26 parts of dipropylene glycol butyl ether, 4 parts of octadecyl amide, 12 parts of salicylic acid, 5 parts of adipic acid, 0.3 parts of silicone surfactant, 0.7 parts of 3-dimethylamino-1,2-propylene glycol, 0.3 parts of 2,6-dibromo-3,4-dichloroaniline, 0.7 parts of triethanolamine hydrochloride, 0.5 parts of dodecyl imidazoline, and 0.5 parts of oleyl hydroxyethyl imidazoline.
[0057] Embodiment 5:
[0058] Nano / micron antimony powder with an average particle size of 1000 μm and tin-based alloy SnAg3Cu0.5 powder are mixed and stirred in proportion to form a mixed powder, and then the mixed powder is mixed and stirred with flux paste F in proportion to form a composite solder paste. In terms of mass percentage, the nano / micron antimony powder in the composite solder paste accounts for 4% of the composite solder paste.
[0059] Among them, solder paste F includes the following ingredients: 45 parts of polymerized rosin, 35 parts of dipropylene glycol butyl ether, 2.5 parts of octadecyl amide, 13 parts of adipic acid, 0.8 parts of silicone surfactant, 3 parts of 3-dimethylamino-1,2-propylene glycol, 0.1 parts of 2,6-dibromo-3,4-dichloroaniline, 0.1 parts of diphenylguanidine hydrobromide, 0.3 parts of lauryl hydroxyethyl imidazoline, and 0.2 parts of oleyl hydroxyethyl imidazoline.
[0060] Embodiment 6:
[0061] Tin-based alloy SnCu0.7 powder and flux paste B are mixed and stirred in proportion to form solder paste, nano / micro antimony powder with an average particle size of 50 μm and flux paste C are mixed and stirred in proportion to form antimony paste, and then the solder paste and antimony paste are mixed and stirred in proportion to form a composite solder paste, in which the nano / micro antimony powder in the composite solder paste accounts for 4% of the composite solder paste in terms of mass percentage.
[0062] Embodiment 7:
[0063] Tin-based alloy SnAg3Cu0.5 powder and flux paste B are mixed and stirred in proportion to form solder paste, nano / micro antimony powder with an average particle size of 50 μm and flux paste C are mixed and stirred in proportion to form antimony paste, and then the solder paste and antimony paste are mixed and stirred in proportion to form a composite solder paste, in which the nano / micro antimony powder in the composite solder paste accounts for 4% of the composite solder paste in terms of mass percentage.
[0064] Then, high melting point zirconium powder with a particle size of 0.2 mm is added to the above composite solder paste, and the mixture is mixed to prepare a composite solder paste with controllable solder layer.
[0065] Embodiment 8:
[0066] Tin-based alloy SnAg3Cu0.5 powder and flux paste B are mixed and stirred in proportion to form solder paste, nano / micro antimony powder with an average particle size of 50 μm and flux paste C are mixed and stirred in proportion to form antimony paste, and then the solder paste and antimony paste are mixed and stirred in proportion to form a composite solder paste, in which the nano / micro antimony powder in the composite solder paste accounts for 4% of the composite solder paste in terms of mass percentage.
[0067] Then, high melting point nickel powder with a particle size of 0.5 mm is added to the above composite solder paste, and the mixture is mixed to prepare a composite solder paste with controllable solder layer.
[0068] Embodiment 9:
[0069] Tin-based alloy SnAg3Cu0.5 powder and flux paste B are mixed and stirred in proportion to form solder paste, nano / micro antimony powder with an average particle size of 50 μm and flux paste C are mixed and stirred in proportion to form antimony paste, and then the solder paste and antimony paste are mixed and stirred in proportion to form a composite solder paste, in which the nano / micro antimony powder in the composite solder paste accounts for 10% of the composite solder paste in terms of mass percentage.
[0070] Embodiment 10:
[0071] Tin-based alloy SnAg3Cu0.5 powder and flux paste B are mixed and stirred in proportion to form solder paste, nano / micro antimony powder with an average particle size of 50 μm and flux paste C are mixed and stirred in proportion to form antimony paste, and then the solder paste and antimony paste are mixed and stirred in proportion to form a composite solder paste, in which the nano / micro antimony powder in the composite solder paste accounts for 25% of the composite solder paste in terms of mass percentage.
[0072] Comparative Example:
[0073] A conventional SnAg3Cu0.5 solder paste is prepared by mixing tin-based alloy SnAg3Cu0.5 powder and solder paste B in a certain proportion.
[0074] The present invention conducted the following related test experiments on the above composite solder paste embodiment and comparative example, and the experimental data are shown in Table 1.
[0075] The steps of Experiment 1 are as follows:
[0076] S1: The original melting range of the embodiments and comparative examples was tested using a DSC device.
[0077] S2: Use a heating device to heat to 225°C, and under the protection of nitrogen, print the embodiment and the comparative example on the board for welding, keep warm for 1 minute, then cool and sample to test the solder melting range after welding. Since this experiment is mainly to test the melting range of the solder after welding, in order to avoid reaction with the welding interface, making it difficult to peel off after welding, affecting the sampling test, welding is performed on an aluminum alloy plate.
[0078] The steps of Experiment 2 are as follows:
[0079] The examples and comparative examples were printed on 10×10 mm 2 On the DBC of the embodiment, another DBC of the same size is mounted on the top, and then heated to 225°C using a heating device, and welded under the protection of nitrogen. After welding, samples are taken to test the void rate after welding. Three samples are welded for each embodiment and comparative example.
[0080] The experimental data of Examples 1 to 10 and Comparative Examples are as follows Figure 1 shown.
[0081] By comparing the melting range data before and after welding of the comparative example with those of Examples 1, 2, 9, and 10, it can be seen that the melting range of the solder paste containing no nano / micron antimony powder cannot be improved before and after welding; the liquidus point of the composite solder paste containing 1.5wt.% of nano / micron antimony powder is improved after welding, but the solidus point is not significantly improved; the solidus point and liquidus point of the composite solder paste containing 4wt.%, 10wt.%, and 25wt.% of nano / micron antimony powder are significantly improved after welding.
[0082] From the ultrasonic scanning microscopy images after welding of the comparative examples and embodiments 1, 2, 9 and 10, it can be seen that with the increase of the content of nano / micro antimony powder, the shape of the voids after welding gradually changes from circular to scale-shaped, which indicates that the wettability of the solder begins to decrease significantly at 25wt.%.
[0083] According to the average solder void rate data of the comparative examples and embodiments 1, 2, 9, and 10, the soldering paste includes: a film-forming substance, an organic amide, an organic carboxylic acid, an organosilicon surfactant, an organic solvent, an organic amine halide, and an alkyl imidazoline corrosion inhibitor, wherein the film-forming substance includes at least one of hydrogenated rosin and polymerized rosin; the organic amide includes octadecylamide, and the organic carboxylic acid includes at least one of malic acid, salicylic acid, and adipic acid; the organic solvent includes at least one of 3-dimethylamino-1,2-propylene glycol and dipropylene glycol butyl ether; the organic amine halide includes at least one of 2,3,4,5-tetrachloroaniline, 2,6-dibromo-3,4-dichloroaniline, ethylenediamine hydrochloride, triethanolamine hydrochloride, and diphenylguanidine hydrobromide; when the alkyl imidazoline corrosion inhibitor includes at least one of lauryl hydroxyethyl imidazoline, dodecyl imidazoline, oleyl hydroxyethyl imidazoline, and heptadecyl imidazoline, the composite solder paste has weldability and can form an effective connection.
[0084] By comparing the experimental data of Examples 2, 3, 4, and 5, it can be seen that the melting range of the composite solder paste with an average particle size of 50 μm, 150 μm, and 200 nm of nano / micro antimony powder is improved before and after welding, while the melting range of the composite solder paste with an average particle size of 1000 μm of nano / micro antimony powder is not significantly improved before and after welding.
[0085] By comparing the experimental data of Example 2 and Example 6, it can be seen that when the composite solder paste using SnCu0.7 tin-based alloy powder is soldered at 225°C, since the tin-based alloy powder does not melt, there is no reaction at the upper and lower interfaces, no effective connection is formed, and the average solder void rate is 0. However, the composite solder paste using SnAg3Cu0.5 tin-based alloy powder can form an effective connection.
[0086] It can be seen from the experimental data of Examples 7 and 8 that adding high melting point Zr and Ni metal powders to the composite solder paste can effectively control the minimum thickness of the solder layer, so that the thickness of the solder layer is consistent with the particle size of the Zr and Ni metal powders.
[0087] The present invention also conducted the following relevant test experiments on the welding parameters during the use of the above-mentioned composite solder paste embodiment 2, and the experimental data are shown in Table 1.
[0088] Serial number Peak temperature(℃) Holding time (minutes) Solder melting range after welding (℃) 1 250 30 228-241 2 250 10 229-241 3 230 30 228-240 4 230 10 229-242 5 225 15 225-239 6 225 7 225-240 7 225 1 225-240
[0089] Table 1 Experimental data of the influence of different welding parameters on the solder melting range after composite solder paste welding
[0090] From the experimental data in Table 1, it can be seen that the peak temperature is between 225-250℃ and the holding time is between 1-30 minutes. The use of composite solder paste for soldering can improve the post-welding melting range. In addition, according to the diffusion theory, the higher the temperature and the longer the time, the greater the driving force that can be provided and the more sufficient the diffusion. Therefore, it can be seen that the peak temperature is above 225℃ and the holding time is above 1 minute, which can achieve the normal use of the composite solder paste.
[0091] In summary, after reading the present invention document, ordinary technicians in this field can make various other corresponding transformation schemes based on the technical scheme and technical concept of the present invention without creative mental work, which all fall within the scope of protection of the present invention.
Claims
1. A high reliability composite solder paste, characterized in that: The invention comprises tin-based alloy powder, nanometer / micrometer antimony powder and solder paste, wherein the solder paste comprises: film-forming substance, organic amide, organic carboxylic acid, organic silicon surfactant, organic solvent, organic amine halide and alkyl imidazoline corrosion inhibitor.
2. A high-reliability composite solder paste according to claim 1, characterized in that: The film-forming substance includes at least one of hydrogenated rosin and polymerized rosin; the organic amide includes octadecanoyl amide, and the organic carboxylic acid includes at least one of malic acid, salicylic acid, and adipic acid; the organic solvent includes at least one of 3-dimethylamino-1,2-propylene glycol and dipropylene glycol butyl ether; the organic amine halide includes at least one of 2,3,4,5-tetrachloroaniline, 2,6-dibromo-3,4-dichloroaniline, ethylenediamine hydrochloride, triethanolamine hydrochloride, and diphenylguanidine hydrobromide; the alkyl imidazoline corrosion inhibitor includes at least one of lauryl hydroxyethyl imidazoline, dodecyl imidazoline, oleyl hydroxyethyl imidazoline, and heptadecyl imidazoline.
3. The high-reliability composite solder paste according to claim 1, characterized in that: The tin-based alloy powder is a Sn-Ag-Cu alloy.
4. The high-reliability composite solder paste according to claim 1, characterized in that: The content of the nanometer / micrometer antimony powder, in terms of mass percentage, accounts for 1.5%-25% of the composite solder paste; the particle size of the nanometer / micrometer antimony powder is less than or equal to 150 μm.
5. A high-reliability composite solder paste according to claim 4, characterized in that: The content of the nanometer / micrometer antimony powder, measured by mass percentage, accounts for 4%-10% of the composite solder paste.
6. The high-reliability composite solder paste according to claim 1, characterized in that: It also includes high melting point alloy powder, wherein the particle size of the high melting point metal powder ranges from 0.05 to 0.5 mm.
7. A method for preparing a high-reliability composite solder paste using the high-reliability composite solder paste according to any one of claims 1 to 6, characterized in that: The following steps are involved: After any two of the tin-based alloy powder, nanometer / micrometer antimony powder and solder paste are mixed and stirred, they are mixed and stirred with a third one, or the tin-based alloy powder, nanometer / micrometer antimony powder and solder paste are mixed and stirred at the same time.
8. The method for preparing a high-reliability composite solder paste according to claim 7, characterized in that: The oxide film on the surface of the nano / micro antimony powder needs to be removed before mixing.
9. A method for using a high-reliability composite solder paste according to any one of claims 1 to 6, characterized in that: The following steps are involved: Print or dispense the composite solder paste on the welding part, place it on the heating device, heat it to above the melting temperature of the tin-based alloy powder, keep it warm in the atmosphere, nitrogen or vacuum environment, and cool it to obtain the welding joint.
10. A method for using the high-reliability composite solder paste according to claim 9, characterized in that: During the welding process, the peak temperature is 225℃-250℃, and the holding time is 1-30 minutes.
Citation Information
Patent Citations
Micrometer / nanometer particle enhanced composite welding flux and preparation method thereof
CN107999994A
Solder paste
CN111902238A
Flux paste and soldering paste capable of realizing low-temperature welding and high-temperature service
CN115971725A
High-precision nano soldering paste and preparation method thereof
CN116140859A
Soldering lug capable of controlling welding seam thickness and preparation method of soldering lug
CN117300433A